No Causal Association Between Coffee Consumption and Risk of Migraine: A Mendelian Randomization Study - Chen, Heng; Zhang, Han; Zheng, Liangrong (Frontiers in Genetics, 2022)
Background and Aims: Coffee consumption has been suggested to increase the risk of migraine. However, causality remains inconclusive. In the present study, we performed two-sample Mendelian randomization(MR) analysis to investigate the causal relationship between coffee consumption and migraine. Methods: We obtained nine single-nucleotide polymorphisms (SNPs) associated with coffee consumption at genome-wide significance (P < 5 × 10-8) from a large genome-wide association study (GWAS) based on the UK Biobank study (included 375,833 individuals). Summary-level data for any migraine (AM) and its subtypes (migraine with aura (MA) and migraine without aura (MO)) were obtained from the largest available GWAS of migraine conducted by the International Headache Genetics Consortium (IHGC) (included 59,674 cases and 316,078 controls). MR estimates were pooled using fixed-effect inverse-variance weighted (IVW) as the main method. Sensitivity analyses were further performed using weighted median, MR-Egger, and MR-PRESSO to assess the robustness of our findings. Results: Genetically-predicted 50% increase of coffee consumption was not causally associated with the risk of AM (odds ratio (OR), 0.97; 95% confidence interval (CI), 0.83–1.14; P = 0.71), MA (OR, 0.81; 95%CI, 0.58, 1.12; P = 0.19), or MO (OR, 0.97; 95%CI, 0.72, 1.30; P = 0.83) in the fixed-effect IVW methods. Sensitivity analyses returned similar results. No directional pleiotropy was found. Conclusion: This MR study does not support a causal relationship between genetically predicted coffee consumption and the risk of migraine. Coffee consumption is likely not a trigger nor a prevention strategy for migraine headaches.